Validitas Media Pembelajaran Matematika Menggunakan Aplikasi Powtoon - Nela Sari Yolanda; Niscaya Laia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
The role of learning media in the learning and teaching process is an integral part that cannot be separated from the world of education. Learning media is anything that can be used to channel messages from senders to recipients, so that they can stimulate students' thoughts, feelings, concerns, and interests to learn. Seeing the importance of media in learning, it is necessary to develop learning media that are valid and suitable for use in the learning process. In an effort to develop learning media, validation is carried out on the media that is being developed, the purpose of validating is to find out and correct errors that exist in the learning media being developed. This study aims to determine the validity of mathematics learning media using the powtoon application. This type of research is research and development (Research and Development). Based on the results of the validation, it shows that the learning media developed is valid, it can be seen from the results of the validity given by the experts (validators), both subject matter experts and language experts. The validation results obtained were 81% for material aspects and 90% for language aspects.